LEAFLET LEARNING MEDIA DESIGN BASED ON LOCAL WISDOM OF CIREBON CULTURE USING THE CANVA APPLICATION - Yopi Nisa Febianti; Nur Jhamila (JURNAL ILMIAH DIDAKTIKA: Media Ilmiah Pendidikan dan Pengajaran, 2023)
This study aims to determine the design of leaflet learning media based on local cultural wisdom in Cirebon for Class VIII social studies subjects at Cirebon Muhammadiyah Middle School, as well as its feasibility. This research uses qualitative research methods with an R&D approach with the ADDIE development model. The research was conducted at the Keraton Kacirbonan, which is a historical place in Cirebon City. The subjects of this research were tour guides and the community around the Keraton Kacirbonan. Miles and Huberman's qualitative data analysis technique was used in steps, namely: data collection, data reduction, data display, and conclusion. The result of this research is the creation of leaflet learning media based on the local wisdom of Cirebon culture, Keraton Kacirbonan as a learning resource for social studies subjects, material on the Plurality of Indonesian Society. Leaflet learning media components include: cover; content of lesson material; history of Keraton Kacirbonan; and practice. This learning media has material suitability in the "Very Good" category, and media suitability in the "Good" category, so it can be concluded that leaflet learning media is suitable for application in learning in schools.